Connectedness and independence of young adults and parents in the digital world: Observing smartphone interactions at multiple timescales using Screenomics. (April 2023) - Sun, Xiaoran; Ram, Nilam; Reeves, Byron; Cho, Mu-Jung; Fitzgerald, Andrew; Robinson, Thomas N.
Background: Young adults' connectedness with and independence from parents have important implications for both their development and family relationships. Although technology plays an increasingly important role in these dynamics, there are few direct observations of how connectedness and independence unfold in the digital world. Little is known of between- and within-person differences in these dynamics. Purpose: This study uses Screenomics to directly observe smartphone interactions between young adults and their parents, and discover whether and how dimensions of connectedness and independence manifest in these interactions at multiple timescales. Research Design, Study Sample, and Data Collection: Screenshot sequences were collected from 10 ethnically diverse young adult (50% female) participants' smartphones every 5 seconds for up to 1 month (total of 457, 905 screenshots). We identified 1413 interaction instances between young adults and their parents (including 359 calls, 1032 messages, and 10 other communication instances). Analysis and Results: Digital ethnographic analysis of screenshots revealed multiple themes related to connectedness (emotional support, logistical and financial support, consistent communication) and independence (parent fostering independence, parent intrusiveness/overinvolvement, and young adults' psychological separation). Quantitative descriptions at different timescales (week, day, hour, moment) revealed within-person and between-person differences in active engagement, reciprocal communication, consistent communication, parent intrusiveness, young adults' reliance on parents' support, and young adults' psychological separation. Conclusion: Findings highlight the need to examine family digital interactions at multiple timescales and the utility of temporally dense and comprehensive Screenomics data in studying social relations.